Anställdas upplevelse av förändringsarbete : En fallstudie om byte av affärssystem i kommunal sektor - Karlström, Sandra; Pakisjärvi-Forsberg, Anna (2013)
Changes occurs in all types of organizations and are often difficult to implement because it is a complicated process that affects all members in an organization and the members needs to create meaning and understanding of the change. The law of public procurement regulates how municipalities manage procurements and this law is the underlying reason why the municipality of this report has gone through a change regarding their ERP system. The purpose of this report is to increase the level of understanding of institutional pressure and the process of sensemaking that employees go through during a change in a municipality. Another purpose is to identify important factors during a process of change and to develop a research model to understand municipalities undergoing a change. The understanding for institutional pressure and the employees’ process of sensemaking are increased by the institutional theory, literature of sensemaking and the experience of the actors’ process of change. This study was conducted in a municipality in northern Sweden where interviews has been the main source of empirical data. The results of this report reveals that municipalities are affected by pressure from institutional mechanisms and that members participation in a process of change affects to which degree they make sense of the situation. Validerat; 20130725 (global_studentproject_submitter)